Respostas

2014-04-05T13:48:27-03:00


a) 1

--------

3a

 b)x+7.x-7

     ----------   = x+7

       x-7


2014-04-05T13:57:23-03:00
Simplifique 
a) 4a²  (dividindo tudo por 4 a²) =   = 0
  12a³                                         3a

b)x²-49 = (x +7) . (x - 7)   (corta (x -7) do numerador com o denominador = (x +7)
     x-7         (x -7)

c)1+2b   = 2b+1             (corta (2b+1) do numerador com o denominador =    1  
   4b²-1    (2b+1) 
 (2b- 1)                                                                        (2b- 1)
1 1 1
calcule a divisão de 2x²-4x+16 por x+2